The Effectiveness of UKS Teacher Training in Samarinda City inImproving Knowledge and Competence in the Implementation ofHealthy Schools - Riyan Ningsih; Ayudhia Rahmawati; Vivi Elfira Elfira; Morin Chaerunnisa (Mulawarman International Conference on Tropical Public Health, 2025)
Background : The Healthy School Program is a strategic effort to form a learning environment that supports the physical, mental, and social health of students. However, its implementation in Samarinda City still faces obstacles to limited sanitation facilities, lack of health education, and weak capacity of UKS coaching teachers. Objective : This study aims to analyze the effectiveness of UKS teacher training on improving knowledge and skills in the implementation of healthy school programs. Research Methods/ Implementation Methods : The study used a pretest-posttest one group design with a total sample of 72 UKS teachers from public and private elementary schools. Data were collected through questionnaires before and after training, then analyzed using the Wilcoxon test (α = 0.05). Results : The results showed a significant increase in participants' knowledge (p = 0.000). The increase of 27.55% shows that training is effective in strengthening the competence of UKS teachers. Conclusion/Lesson Learned : This participatory-based training also encourages cross-sector collaboration between universities and local governments in strengthening the Healthy School Movement program.